1999
DOI: 10.1029/1999jd900241
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the vertical and regional variability of aerosol optical properties over central and eastern North America

Abstract: Abstract. Aerosol optical properties were measured in situ from a research aircraft during three recent field experiments in the central and eastern parts of North America as well as over areas of the western Atlantic Ocean. Regional and vertical variability of the aerosol properties for boundary layer and free tropospheric air were determined. In general, the differences between distributions of aerosol properties measured at low (planetary boundary layer) and high (free troposphere) altitudes were small but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 25 publications
(14 reference statements)
8
81
1
Order By: Relevance
“…reported previously for both aethalometer (Bodhaine et al, 1991;Clarke et al, 1997) and Radiance Research particle soot absorption photometer (Sheridan and Ogren, 1999;Collins et al, 2000b) measurements. Pressure induced distortions of the filters within the instruments are suspected to underlie the observed behavior (Hansen, 2002).…”
Section: Black Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…reported previously for both aethalometer (Bodhaine et al, 1991;Clarke et al, 1997) and Radiance Research particle soot absorption photometer (Sheridan and Ogren, 1999;Collins et al, 2000b) measurements. Pressure induced distortions of the filters within the instruments are suspected to underlie the observed behavior (Hansen, 2002).…”
Section: Black Carbonmentioning
confidence: 99%
“…However, while satellite instruments offer the advantage of extended coverage in time and space, calibration of the retrieval products is still necessary and ideally requires three-dimensional in situ measurements for appropriate comparisons. Aircraft observations afford the principal advantage of yielding detailed information on aerosol properties with height, albeit within short time periods over geographic areas of limited extent, thereby enabling the question of inhomogeneities of aerosol properties in the vertical to be addressed (Kim et al, 1993a;Pinnick et al, 1993;Raga and Jonas, 1995;Clarke et al, 1996;Sheridan and Ogren, 1999). Airborne observations that are sufficiently comprehensive to inter-relate the optical, physical, and chemical properties of particulates have been carried out relatively infrequently.…”
Section: Introductionmentioning
confidence: 99%
“…These factors were modeled by using several variables in the regression model. Airborne and ground-level measurements have shown that the majority of particle mass loading resides in the lower troposphere and the particle mass distribution below the planetary boundary layer tends to be more homogeneous due to the active mixing (19)(20)(21)(22). Therefore, GEOS-3 PBL data were included in the regression model as a continuous variable to represent particle vertical distribution.…”
Section: Introductionmentioning
confidence: 99%
“…b = σbsp/σsp. This parameterization, presented by Sheridan and Ogren (1999), omits the dependence of β with the zenith angle. The radiative forcing efficiency for daytime-average was calculated with Eqn.…”
Section: Description Of In-situ Variablesmentioning
confidence: 99%
“…The ω0 is part of the radiative forcing per unit of optical depth (ΔRF/δae) at the top of the atmosphere, called radiative forcing efficiency after Sheridan and Ogren (1999). The ΔRF/δae depends on the aerosol size through the upscatter fraction β, the scattering and absorption through ω0, and on seven geophysical quantities.…”
Section: Description Of In-situ Variablesmentioning
confidence: 99%